Penerapan Budaya Kaizen (5R) Sebagai Upaya Peningkatan Mutu Pelayanan Di Rumah Sakit - Leo Pratama Agung; Dety Mulyanti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Quality health services is one measure of satisfaction effect on the patient's desire to return to the institution that provides it effective health services. To meet the needs and desires of patients so that satisfaction can be obtained in the end can increase trust in the hospital through excellent service. One of the important issues to answer the strategy in the midst of a situation of decreased public trust in hospital services is